UNIMAS REHAB CARE - Yong, Pei Yan (Universiti Malaysia Sarawak (UNIMAS), 2019)
UNIMAS Rehab Care Web Application is developed for UNIMAS Rehab clinic to manage their daily operation in a computerized way. It is designed to connect the doctors and the physiotherapists in order to handle the record of patients from registration process to billing process. A structured medical database is designed to maintain patient record and at the same time to improve data retrieval and security. It is designed to have role-based access control where user has their own role and authorization to access the information in the application. The significance of the project is to ease the appointment making process by keeping track of all patients’ appointment schedule. At the same time, it is designed to handle consultation, treatment, reporting as well as billing process. Besides, reminder of appointment will be sent via email to notify patients about their appointment.